Undertaking Studies Within A Trial to evaluate recruitment and retention strategies for randomised controlled trials: lessons learnt from the PROMETHEUS research programme - Parker, Adwoa; Arundel, Catherine; Clark, Laura; Coleman, Elizabeth; Doherty, Laura; Hewitt, Catherine Elizabeth; Beard, David; Bower, Peter; Cooper, Cindy; Culliford, Lucy; Devane, Declan; Emsley, Richard; et al. (Health technology assessment (Winchester, England), 2024)
Randomised controlled trials ('trials') are susceptible to poor participant recruitment and retention. Studies Within A Trial are the strongest methods for testing the effectiveness of strategies to improve recruitment and retention. However, relatively few of these have been conducted. PROMoting THE Use of Studies Within A Trial aimed to facilitate at least 25 Studies Within A Trial evaluating recruitment or retention strategies. We share our experience of delivering the PROMoting THE Use of Studies Within A Trial programme, and the lessons learnt for undertaking randomised Studies Within A Trial. A network of 10 Clinical Trials Units and 1 primary care research centre committed to conducting randomised controlled Studies Within A Trial of recruitment and/or retention strategies was established. Promising recruitment and retention strategies were identified from various sources including Cochrane systematic reviews, the Study Within A Trial Repository, and existing prioritisation exercises, which were reviewed by patient and public members to create an initial priority list of seven recruitment and eight retention interventions. Host trial teams could apply for funding and receive support from the PROMoting THE Use of Studies Within A Trial team to undertake Studies Within A Trial. We also tested the feasibility of undertaking co-ordinated Studies Within A Trial, across multiple host trials simultaneously. Clinical trials unit-based trials recruiting or following up participants in any setting in the United Kingdom were eligible. Clinical trials unit-based teams undertaking trials in any clinical context in the United Kingdom. Funding of up to £5000 and support from the PROMoting THE Use of Studies Within A Trial team to design, implement and report Studies Within A Trial. Number of host trials funded. Forty-two Studies Within A Trial were funded (31 host trials), across 12 Clinical Trials Units. The mean cost of a Study Within A Trial was £3535. Twelve Studies Within A Trial tested the same strategy across multiple host trials using a co-ordinated Study Within A Trial design, and four used a factorial design. Two recruitment and five retention strategies were evaluated in more than one host trial. PROMoting THE Use of Studies Within A Trial will add 18% more Studies Within A Trial to the Cochrane systematic review of recruitment strategies, and 79% more Studies Within A Trial to the Cochrane review of retention strategies. For retention, we found that pre-notifying participants by card, letter or e-mail before sending questionnaires was effective, as was the use of pens, and sending personalised text messages to improve questionnaire response. We highlight key lessons learnt to guide others planning Studies Within A Trial, including involving patient and public involvement partners; prioritising and selecting strategies to evaluate and elements to consider when designing a Study Within A Trial; obtaining governance approvals; implementing Studies Within A Trial, including individual and co-ordinated Studies Within A Trials; and reporting Study Within A Trials. The COVID-19 pandemic negatively impacted five Studies Within A Trial, being either delayed ( = 2) or prematurely terminated ( = 3). PROMoting THE Use of Studies Within A Trial significantly increased the evidence base for recruitment and retention strategies. When provided with both funding and practical support, host trial teams successfully implemented Studies Within A Trial. Future research should identify and target gaps in the evidence base, including widening Study Within A Trial uptake, undertaking more complex Studies Within A Trial and translating Study Within A Trial evidence into practice. All Studies Within A Trial in the PROMoting THE Use of Studies Within A Trial programme had to be registered with the Northern Ireland Network for Trials Methodology Research Study Within A Trial Repository. This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 13/55/80) and is published in full in ; Vol. 28, No. 2. See the NIHR Funding and Awards website for further award information.